Shifting, Not Changing: Adaptive Continuity in Indonesia’s Educational Policy Innovation Toward Quality Learning. - Sumarta; Sarwo Edy; Rosidin; Dinata Firmansyah (Lentera Pendidikan: Jurnal Ilmu Pendidikan dan Keguruan Islam, 2025)
This study aims to unpack the paradigm of "new minister, new policy" in the innovation of educational policy in Indonesia and to analyze the "shifting, not changing" approach promoted by the Minister of Primary and Secondary Education, Prof. Abdul Muti, in the pursuit of quality learning. The research design employed is qualitative policy analysis, focusing on a case study of Prof. Muti’s ideas and policies. The main findings indicate that the "shifting, not changing" approach—rooted in the principle of al-muhafazah ‘ala al-qadim al-shalih wa al-akhdzu bi al-jadid al-aslah (preserving the good from the past and adopting the better from the new)—seeks to create adaptive policy continuity while avoiding radical overhauls. The implication of this research is that sustainable educational policy can be achieved through innovative conservation, in which the positive elements of previous policies are maintained while integrating updates relevant to 21st-century needs. This has the potential to reduce resistance to change and build stability within the educational system. The originality of this study lies in its in-depth analysis of the philosophy and practical implementation of the "shifting, not changing" approach as a solution to the unproductive cycle of policy change, offering an alternative framework for educational innovation in Indonesia.